PENGARUH PENGGUNAAN SBR LATEX TERHADAP KUAT TEKAN DAN MODULUS ELASTISITAS BETON POROUS DENGAN MENGGUNAKAN RCA (RECYCLED COARSE AGGREGATE) - Siregar, Julius; Arifi, Eva (Jurnal Mahasiswa Jurusan Teknik Sipil, 2021)
The use of conventional concrete, which continues to increase along with the rapid development ofinfrastructure in Indonesia, has resulted in a more extensive waterproof layer. One solution that canovercome this problem is porous concrete using recycled coarse aggregate or RCA (Recycled CoarseAggregate). However, porous concrete has a disadvantage, there is a weak bond between aggregates.In this research, the compressive strength of concrete tested with SBR Latex variations of 5% and 10%of cement weight and variations of recycled coarse aggregate 0% and 100%. Concrete compressivestrength testing is in accordance with SNI 03-1974-1990. Apart from that, test of content weight,specific gravity, absorption, and void ratio is based on SNI 1969: 2008, ASTM C29, and ASTM C1688.Making concrete samples using a cement mix ratio with aggregate of 1: 4 and a cement water factor(FAS) value of 0.27.The use of RCA in porous concrete resulted in a decrease in the compressive strength of porousconcrete compared to NCA and the modulus of elasticity of RCA was lower than NCA. This is due to thelower quality of RCA than NCA. The use of SBR Latex can increase the compressive strength ofconcrete. In tested porous concrete with 5% SBR latex, there was an increase in the compressivestrength of the concrete by 15.21% with NCA and 22.3% with RCA. Porous concrete with the additionof 10% SBR latex, there was an increase of 47.5% in with NCA and 65.87% with of RCA.Keywords: porous concrete, recycled coarse aggregate, SBR Latex, compressive strength of concrete,modulus of elasticity